New species of Rhyacodrilus (Annelida: Clitellata: Rhyacodrilinae) of North America, with re-description of R. sodalis (Eisen, 1879) - Rodriguez, Pilar; Fend, Steven V. (Zootaxa, 2013)
Six new Nearctic species of the aquatic oligochaete genus Rhyacodrilus (Annelida, Clitellata, Rhyacodrilinae), are de-scribed, five (R. saelonae sp. n., R. quileuticus sp. n., R. clio sp. n., R. alcyoneus sp. n. and R. longichaeta sp. n.) from western and one (R. propiporus sp. n.) from eastern North America. The taxonomy of the most common Rhyacodrilus species reported in the Nearctic region has been based largely on chaetal characters, which has generated certain confu-sion. The new species give a new perspective on the genus Rhyacodrilus in North America, suggesting a much higher diversity than previously expected. The description of R. longichaeta sp. n. questions the taxonomic status of R. montana (Brinkhurst), which is here regarded as species inquirenda. The taxonomic status of R. sodalis (Eisen) is discussed based on characters of the reproductive system, the existing Lake Tahoe neotype series is invalidated, and a neotype is described from Eisen’s type locality. Based on the discussion of the characters of the genus Rhyacodrilus, the genus Stochidrilus Martínez-Ansemil et al. is proposed as a junior synonym of that genus. The presence of the widely reported species R. coccineus has not been confirmed in the study collections, although the species requires a sound revision. A key to the species bearing hair chaetae is provided, based mainly on features of the reproductive system.